Outcomes of Late Presenters with Acute Inferior Wall Myocardial Infarction Complicated by Complete Heart Block Treated with Percutaneous Coronary Intervention - Syed Tahir Shah, Ibrahim Shah, Noor Ul Hadi, Muhammad Abdur Rauf, Tariq Nawaz, Sana Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study was to evaluate the outcomes of delayed presenters with acute inferior wall MI complicated by complete heart block treated by PCI of culprit artery. Methods: A descriptive cross-sectional study conducted on 40 patients with late presentation of either 48 hours or more with acute inferior wall MI complicated by complete heart block were included. All patients underwent coronary angiography and PCI of culprit vessel attempted. Outcomes were measured in terms of restoration of normal sinus rhythm along with heart block recovery time, requirement for implantation of permanent pacemaker and in hospital mortality. The statistical analysis was performed using SPSS 24. Results: The mean age was 55.73 ± 7.679. Male were 65% (n=26), diabetes 62.5% (n=25), hypertension 57.5 (n=23), smoking 30% (n=12) and dyslipidemia 52.5% (n=21). Mean delay in presentation 69.35 ± 11.132 hours. Mean restoration time 69.25 ± 10.95 hours, with minimum of 48 hrs & maximum 86 hrs. Mean tropinin I level 1588.97± 996.70 pg/ml. Mean Ejection fraction 44.8± 9.48 %. Successful PCI has a significant correlation with recovery time (p=.004). There was no in hospital mortality. All restores normal sinus rhythm and no patient needed permanent pacemaker. Successful PCI has a significant correlation with recovery time (p=.004). Conclusion: Successful PCI of culprit artery in late presenter of CHB with acute inferior MI results in restoration of NSR all patients with reduction in heart block recovery time and no in hospital death. Keywords: Acute inferior wall MI, Complete heart block, PCI, late presenter